2008
DOI: 10.1073/pnas.0708940105
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and splenomegaly in cGKI-deficient mice

Abstract: To explore the functional significance of cGMP-dependent protein kinase type I (cGKI) in the regulation of erythrocyte survival, gene-targeted mice lacking cGKI were compared with their control littermates. By the age of 10 weeks, cGKI-deficient mice exhibited pronounced anemia and splenomegaly. Compared with control mice, the cGKI mutants had significantly lower red blood cell count, packed cell volume, and hemoglobin concentration. Anemia was associated with a higher reticulocyte number and an increase of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
115
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 60 publications
6
115
0
1
Order By: Relevance
“…Eryptosis is stimulated by increase in cytosolic Ca 2+ activity [5,11,12,19,41]. Phosphatidylserine-exposing erythrocytes are engulfed by macrophages and are thus rapidly eliminated from circulating blood [24,26,36]. Cytosolic Ca 2+ concentration is increased by activation of Ca 2+ -permeable cation channels [20,21,32,41].…”
Section: Introductionmentioning
confidence: 99%
“…Eryptosis is stimulated by increase in cytosolic Ca 2+ activity [5,11,12,19,41]. Phosphatidylserine-exposing erythrocytes are engulfed by macrophages and are thus rapidly eliminated from circulating blood [24,26,36]. Cytosolic Ca 2+ concentration is increased by activation of Ca 2+ -permeable cation channels [20,21,32,41].…”
Section: Introductionmentioning
confidence: 99%
“…Nitroxide is partially effective through activation of cGMP-dependent protein kinases (106)(107)(108). The mechanism is apparently effective under control conditions in vivo, as mice deficient of the cGMP-dependent protein kinase type I (cGKI) suffer from severe anaemia and splenomegaly (109).…”
Section: Inhibitors Of Eryptosismentioning
confidence: 99%
“…3,4 Immunocytochemistry of bone marrow indicated that macrophages but not erythroblasts express cGKI. 1 In contrast, it was found that erythroblasts and erythrocytes purified by immunomagnetic selection using labeled anti-Ter119 MicroBeads followed by magnetic cell sorting are cGKI positive.…”
mentioning
confidence: 99%
“…Histological inspection indicated an increased erythrocyte content of the spleen, as reported by Föller and colleagues. 3 The spleen size and spleen weight were normalized by treatment with the PPI ( Figure 3A) in the cGKI -/-and cGKI RM mice. The iron content of the spleen was increased by either PPI treatment or iron injection, and was normalized by the com- …”
mentioning
confidence: 99%
See 1 more Smart Citation